2013
DOI: 10.1002/pmic.201200356
|View full text |Cite
|
Sign up to set email alerts
|

Secretome proteins as candidate biomarkers for aggressive thyroid carcinomas

Abstract: Using proteomics in tandem with bioinformatics, the secretomes of nonaggressive and aggressive thyroid carcinoma (TC) cell lines were analyzed to detect potential biomarkers for tumor aggressiveness. A panel of nine proteins, activated leukocyte cell adhesion molecule (ALCAM/CD166), tyrosine-protein kinase receptor (AXL), amyloid beta A4 protein, amyloid-like protein 2, heterogeneous nuclear ribonucleoprotein K, phosphoglycerate kinase 1, pyruvate kinase isozyme M2, phosphatase 2A inhibitor (SET), and protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…In this respect, tumor suppressor protein 14-3-3-σ was reported to downregulate in a radioresistant nasopharyngeal cancer cell line when compared with regular nasopharyngeal cancer cell line,[30] and the same trend was observed for non-small cell lung cancer cells in comparison with normal human bronchial epithelial cells [31]. In addition, secreted 14-3-3 zeta has been demonstrated to have potential as candidate biomarkers for aggressive thyroid carcinomas [32]. The seven 14-3-3 proteins (see Supporting Information Table S1) observed in this work all showed downregulation for all of the irradiated samples, in particular for the 200 cGy dose when compared with the sham irradiation, which showed that ionizing radiation suppress expression of many proteins within the 14-3-3 family, this may lead to perturbed homeostasis in tumor suppression and other important biological functions.…”
Section: Resultsmentioning
confidence: 68%
“…In this respect, tumor suppressor protein 14-3-3-σ was reported to downregulate in a radioresistant nasopharyngeal cancer cell line when compared with regular nasopharyngeal cancer cell line,[30] and the same trend was observed for non-small cell lung cancer cells in comparison with normal human bronchial epithelial cells [31]. In addition, secreted 14-3-3 zeta has been demonstrated to have potential as candidate biomarkers for aggressive thyroid carcinomas [32]. The seven 14-3-3 proteins (see Supporting Information Table S1) observed in this work all showed downregulation for all of the irradiated samples, in particular for the 200 cGy dose when compared with the sham irradiation, which showed that ionizing radiation suppress expression of many proteins within the 14-3-3 family, this may lead to perturbed homeostasis in tumor suppression and other important biological functions.…”
Section: Resultsmentioning
confidence: 68%
“…The results showed a proteomic signature specific for the ATC cells, correlated with their high proliferation rate, motility propensity and metabolic shift, in respect to the BCPAP cells. The secretome of non-aggressive and aggressive thyroid cell lines (BCPAP, SW1736 and C643) was also investigated by liquid chromatography-MS for the same purpose [100]. The expression of nine proteins was also evaluated in sera and tissue by the enzyme-linked immunosorbent assay (ELISA) and immunohistochemistry, respectively.…”
Section: Proteomics On Thyroid Cells Linesmentioning
confidence: 99%
“…In the field of thyroid cancer, proteomics has been initially applied on thyroid tissue specimens and cancer cell lines [80,81,82,83,84,85,86,87,88,89], using different techniques such as surface-enhanced laser desorption/ionization-time-of-flight-mass spectrometry (SELDI-TOF-MS), liquid chromatography–mass spectrometry (LC/MS) and MS alone. All these studies ended by identifying specific protein signatures for malignant and benign lesions with a final selection of clusters of proteins with discriminating abilities.…”
Section: Proteomics: An Interesting Alternative Approach To Stratimentioning
confidence: 99%